Editöryal Yorum St. Jude Silzone mekanik kalp kapaklarında paravalvüler kaçak ve emboli riski - (:unkn) unknown (My University, 2006)
0
Editorial Comment Paravalvular leak and embolic risks in silzone-coated mechanical heart valves
Keywords: Kalp ve Kalp Damar Sistemi